Pulsed Electromagnetic Field (PEMF) stimulation as an adjunct to exercise: a brief review - Ghanbari Ghoshchi, Sheyda; Petroni, Maria Letizia; Piras, Alessandro; Marcora, Samuele Maria; Raffi, Milena (Frontiers in Sports and Active Living, 2024)
Pulsed Electromagnetic Field (PEMF) therapy is a non-invasive treatment that utilizes electromagnetic fields to stimulate and promote natural healing processes within the body. PEMF therapy works by emitting low-frequency electromagnetic pulses, which penetrate deep into tissues and cells, enhancing cellular function and health. PEMF applications are vast, ranging from enhancing recovery in athletes to supporting overall well-being in everyday individuals. PEMF therapy is increasingly recognized in the realm of sports and physical activity for its profound benefits in enhancing performance, accelerating recovery, and preventing injuries. By improving circulation, enhancing tissue oxygenation, and promoting the body's natural healing processes, PEMF therapy has become an invaluable tool in sports medicine, contributing to optimized physical health and prolonged athletic careers. In this review, we explore the effects of PEMF on exercise and the underlying physiological mechanisms.